Educational Program and Motor Coordination Development in Youth Soccer: Program Pendidikan dan Pengembangan Koordinasi Motorik dalam Sepak Bola Pemuda - Shneair, Thaer Saleh; Ghali, Abed Sarwal; Hadi, Ali Kadhim (Indonesian Journal of Education Methods Development, 2025)
Background: Developing motor coordination and sensory perception is essential for skill mastery in youth soccer. Specific Background: Traditional training often isolates technical skills without integrating perception and coordination. Knowledge Gap: Limited studies have examined the holistic educational programs targeting these three dimensions simultaneously. Aims: This study aimed to determine the effectiveness of an educational program in developing motor coordination, sensory perception, and scoring accuracy among youth soccer players. Results: The findings revealed significant improvement in all three variables for the experimental group compared to the control group, confirming the program’s efficiency. Novelty: The study introduces an integrated training approach combining motor and sensory learning principles. Implications: These results suggest that structured educational programs can enhance both physiological and perceptual components in young athletes, supporting comprehensive motor development in soccer. Highlights:• Integrated educational training improved coordination and scoring accuracy.• Sensory perception development contributed to performance precision.• Supports holistic training in youth soccer programs. Keywords:Motor Coordination, Sensory Perception, Scoring Accuracy, Educational Program, Youth Soccer